Research on the Application of Nano-Additives in Gel-like Lubricants - Han Peng; Zihao Meng; Linjian Shangguan; Lei Liu; Can Yang; Lingxi Guo (Gels)
In the field of mechanical motion, friction loss and material wear are common problems. As one of the essential components for enhancing the lubricating performance of gel-like lubricants, nano-additives leverage their unique physical and chemical properties to form an efficient protective film on friction surfaces. This effectively reduces friction resistance and inhibits wear progression, thereby playing a significant role in promoting energy conservation, emissions reduction, and the implementation of green development principles. This study first introduces the physical and chemical preparation processes of gel-like lubricant nanoadditives. It then classifies them (mainly based on metal bases, metal oxides, nanocarbon materials, and other nanoadditives). Then, the performance of gel-like lubricant nano-additives is evaluated (mainly in terms of anti-wear, friction reduction, oxidation resistance, and load carrying capacity), and the surface analysis technology used is described. Finally, we summarize the application scenarios of gel-like lubricant nano-additives, identify the challenges faced, and discuss future prospects. This study provides new insights and directions for the design and synthesis of novel gel-like lubricants with significant lubricating and anti-wear properties in the future.